Super Refractory Status Epilepticus in Hashimoto’s Encephalopathy - Mujahid Al-Busaidi; Jyoti Burad; Asma Al-Belushi; Arun Gujjar (Oman Medical Journal, 2017)
We present a case of a 38-year-old woman who was at eight weeks of gestation and was admitted to Sultan Qaboos University Hospital with refractory status epilepticus (SE). She presented with a two-day history of fever and a depressed level of consciousness that was followed with generalized tonic-clonic seizures. She progressed to refractory SE that required intubation and mechanical ventilation. Autoimmune workup was suggestive of Hashimoto’s encephalopathy (HE) as suggested by the high levels of thyroid antibodies. Her magnetic resonance imaging showed bilateral hippocampal and basal ganglia hyperintensities, and electroencephalogram showed bilateral frontal epileptiform discharges. Other autoimmune workup was negative. Intravenous anesthetics were started including propofol, midazolam, ketamine, and thiopentone. She was started on multiple immunosuppressive therapies. Multiple antiepileptics were used including phenytoin, lamotrigine, levetiracetam, sodium valproate, clobazam, phenobarbital, and lacosamide. The outcome was unusual in terms of refractoriness to immunotherapy treatment despite a confirmed diagnosis. We did a literature review of all cases with HE presenting with SE with their clinical characteristics and outcome.